The association between elevated serum interleukin‐22 and the clinical diagnosis of axial spondyloarthritis: A retrospective study. (22nd November 2021) - Sagiv, Michal; Adawi, Mohammad; Awisat, Abid; Shouval, Aniela; Peri, Regina; Sabbah, Firas; Rosner, Itzhak; Kessel, Aharon; Slobodin, Gleb
Abstract: Objective: There is an unmet need for a reliable biomarker for the differentiation of axial spondyloarthritis (AxSpA) from its mimickers. Serum levels of interleukin‐22 (IL‐22) have previously been found to be significantly elevated in patients with AxSpA compared with healthy individuals or persons with osteoarthritis. Methods: Consecutive patients with established or suspected AxSpA were enrolled. The clinical data, as well as results of laboratory and imaging studies, were acquired from patients' charts. The final diagnosis of definite or probable SpA, or an alternative diagnosis, was determined, and the serum levels of IL‐22 were examined by enzyme‐linked immunosorbent immunoassay. Results: Interleukin‐22 levels were significantly higher in patients with definite AxSpA (29 patients) compared with patients with alternative diagnoses (14 patients) and healthy volunteers (16 individuals; P  < 0.001 for both comparisons). The sensitivity and specificity of the serum IL‐22 for the AxSpA diagnosis were 0.68 (95% CI 0.49‐0.84) and 0.86 (95% CI 0.68‐0.95), respectively, for the cut‐off value of 5 pg/mL. In patients with AxSpA, serum IL‐22 levels did not correlate with modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Ankylosing Spondylitis Disease Activity Score (ASDAS), or serum C‐reactive protein. Conclusion: Serum IL‐22 levels are elevated in patients with the clinical diagnosis of AxSpA and can potentially serve as an independent biomarker for the differentiation of AxSpA from its non‐inflammatory mimickers.